Odwrotne obligacje zamienne na akcje jako instrument pozyskiwania i inwestowania kapitału - Mamcarz, Henryk (Reverse Convertible Bonds as an Instrument of Raising and Investing od Capital, 2006)
Straight bond is an underlying instrument for creating two financial instruments of a complex I structure: convertible bonds and reverse convertible bonds. The latter kind of bonds is a financial I innovation constituting a combination of the straight bond and the put option written by the investor lo (he issuer. On the bond maturity day the issuer has the right to buy it out for cash or to convert it I for shares. The issuer pays the investor for this right (the put option), enclosing an interest coupon in the bond, the value of the coupon being above the interest rate of the capital market. The issuer chooses the way of sinking of the bond comparing the value of the block of shares on the maturity day with the face value of the reverse bond. As a result, the way of exercising the option by the issuer and thereby the profitability of an investment is determined by the price of shares on the maturity day. The investor, on buying the reverse convertible bond additionally ought to compare the current value of the built-in option with its fair value and, if necessary, consider whether the purchase of the straight bond and writing the put option for shares is not a better investment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 420-427